THE APPLICATION OF SUPRATHRESHOLD STOCHASTIC RESONANCE TO COCHLEAR IMPLANT CODING - STOCKS, N. G.; ALLINGHAM, D.; MORSE, R. P. (Fluctuation and noise letters, 2002)
In this paper we explore the possibility of using a recently discovered form of stochastic resonance - termed suprathreshold stochastic resonance - to improve speech comprehension in patients fitted with cochlear implants. A leaky-integrate-and-fire (LIF) neurone is used to model cochlear nerve activity when subject to electrical stimulation. This model, in principle, captures key aspects of temporal coding in analogue cochlear implants. Estimates for the information transmitted by a population of nerve fibres is obtained as a function of internal (neuronal) noise level. We conclude that SSR does indeed provide a possible mechanism by which information transmission along the cochlear nerve can be improved - and thus may well lead to improved speech comprehension.